Efficacy of group biofeedback treatment on hyperemesis gravidarum with psychosomatic symptoms diagnosed with the revised version of Diagnostic Criteria for Psychosomatic Research (DCPR-R): study protocol for a randomised controlled trial. Issue 3 (31st March 2022) - Cui, Xuelian; Cao, Jianxin; Rafanelli, Chiara; Zhu, Boheng; Gostoli, Sara
Abstract : Introduction: Hyperemesis gravidarum (HG) is a condition characterised by dehydration, electrolyte imbalance, lack of nutrition and at least 5% loss in body weight, occurring in the first half of pregnancy. The aim of this trial is to examine the efficacy of group biofeedback treatment on patients with HG with psychosomatic symptoms, which will be evaluated through the revised version of Diagnostic Criteria for Psychosomatic Research (DCPR-R). Methods and analysis: In this single-blinded randomised controlled clinical trial, 68 patients with HG diagnosed with at least one psychosomatic syndrome according to DCPR-R and aged 18–40 years, will be recruited in a Chinese Maternal and Child Health Hospital. The sample will be randomised (1:1) into two arms: experimental group, which will undergo group biofeedback treatment, psycho-education and treatment as usual (TAU); and control group, which will undergo psycho-education and TAU only. The primary outcomes will be reduction of the frequency of psychosomatic syndromes, severity of nausea/vomiting, quality of life and heart rate variability. The secondary outcomes will include days of hospitalisation, repeated hospitalisation and laboratory investigations. Ethics and dissemination: This study has received ethical approval from the Nanjing Medical University (No. 2019/491, granted 22 February 2019). All participants will be required to provide written informed consent. Study outcomes will be disseminated through peer-reviewed publications and academic conferences, and used to confirm a tailored biofeedback intervention for patients with HG with psychosomatic symptoms. Trial registration number: Chinese Clinical Trial Registry (ChiCTR2000028754).